A Bayesian perspective on magnitude estimation. Issue 5 (May 2015) - Petzschner, Frederike H.; Glasauer, Stefan; Stephan, Klaas E.
Highlights A generic Bayesian framework explains regression, range, and sequential effects. Weber-Fechner law and Stevens' power law can be linked via Bayes' Rule. Stevens' power law exponent can be reinterpreted as weighting of prior knowledge. We link Bayesian explanations of magnitude estimation to theories of schizophrenia.